Hippocampal CA1 activity correlated with the distance to the goal and navigation performance. Issue 9 (14th December 2017) - Spiers, Hugo J.; Olafsdottir, H. Freyja; Lever, Colin
Abstract: Coding the distance to a future goal is an important function of a neural system supporting navigation. While some evidence indicates the hippocampus increases activity with proximity to the goal, others have found activity to decrease with proximity. To explore goal distance coding in the hippocampus we recorded from CA1 hippocampal place cells in rats as they navigated to learned goals in an event arena with a win‐stay lose‐shift rule. CA1 activity was positively correlated with the distance ‐ decreasing with proximity to the goal. The stronger the correlation between distance to the goal and CA1 activity, the more successful navigation was in a given task session. Acceleration, but not speed, was also correlated with the distance to the goal. However, the relationship between CA1 activity and navigation performance was independent of variation in acceleration and variation in speed. These results help clarify the situations in which CA1 activity encodes navigationally relevant information and the extent to which it relates to behavior.